LOOKING FOR THE ROOT CAUSES OF THE HINDU LEADERSHIP CRISIS IN INDONESIA - I Made Deddy Sandrawan, (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
Hinduism actually has many leadership teachings that are of high value and are still relevant, but in reality there is a crisis of leadership with a Hindu character. This research explores the form of leadership with a Hindu character, the factors that caused the crisis and how to solve it. Apart from aiming to popularize Hindu leadership characteristics, it is hoped that it will provide benefits for the Hindu community to better understand the teachings of their religion in the field of leadership. In the context of the nation and state, contribute to elevating leadership concepts in the Hindu tradition as a solution option for the national leadership crisis. The concept of Raja Rshi is an ideal leadership concept that combines the character of a leader as a King as well as being wise and wise like a Rshi. The root of the Hindu leadership crisis is the weakness of the basic Hindu character education pattern at an early age. Other factors are the country's political system which is no longer in accordance with Pancasila democracy and the implementation of regional autonomy in districts. The struggle for political power based on the majority of votes gives rise to many problems. Politics that relies on the dominant role of political parties also causes the death of the leadership cadre process. Regional autonomy only produces small kings in the regions which weaken the leadership structure in the regions. The way out of this leadership crisis is to start with serious improvements in basic education and continue with other efforts.